Transcriptomic Analysis Reveals Important Roles of Lignin and Flavonoid Biosynthetic Pathways in Rice Thermotolerance During Reproductive Stage - Cai, Zhenzhen; He, Fengyu; Feng, Xin; Liang, Tong; Wang, Hongwei; Ding, Shuangcheng; Tian, Xiaohai (Frontiers in Genetics, 2020)
Rice is one of the major staple cereals in the world, but heat stress is increasingly threatening its yield. Analyzing the thermotolerance mechanism from new thermotolerant germplasms is very important for rice improvement. Here, physiological and transcriptome analyses were used to characterize the difference between two germplasms, heat-sensitive MH101 and heat-tolerant SDWG005. Two genotypes exhibited diverse heat responses in pollen viability, pollination characteristics, and antioxidant enzymatic activity in leaves and spikelets. Through cluster analysis, the global transcriptomic changes indicated that the ability of SDWG005 to maintain a steady-state balance of metabolic processes played an important role in thermotolerance. After analyses of gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment, we found that the thermotolerance mechanism in SDWG00 was associated with reprogramming the cellular activities, such as response to abiotic stress and metabolic reorganization. In contrast, in MH101 variety, the down-regulation genes associated with DNA replication and DNA repair proofreading could cause serious injury to reproductive development when exposed to high temperature during meiosis. Furthermore, we identified 77 and 11 differentially expressed genes (DEGs) involved in lignin and flavonoids biosynthesis from the most significantly enriched phenylpropanoid biosynthesis pathway, respectively. Moreover, we found that more lignin deposition and flavonoids accumulation happened in SDWG005 than in MH101 under heat stress. The results indicated that lignin and flavonoid biosynthetic pathways might play important roles in rice heat resistance during meiosis.